2012
DOI: 10.1371/journal.pone.0033232
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Mouse Skeletal Muscle to Long-Term Microgravity in the MDS Mission

Abstract: The effect of microgravity on skeletal muscles has so far been examined in rat and mice only after short-term (5–20 day) spaceflights. The mice drawer system (MDS) program, sponsored by Italian Space Agency, for the first time aimed to investigate the consequences of long-term (91 days) exposure to microgravity in mice within the International Space Station. Muscle atrophy was present indistinctly in all fiber types of the slow-twitch soleus muscle, but was only slightly greater than that observed after 20 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
145
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 154 publications
(178 citation statements)
references
References 64 publications
24
145
1
1
Order By: Relevance
“…Exposure to microgravity or hind limb unloading of rodents causes passive shortening of soleus muscle due to ankle plantarflexion (20,39,59), which reduces the mechanical stress (20) and neural activity (19,20,39,43). Even though it is well-reported that muscles composed predominantly of slowtwitch fibers are more susceptible to unloading-related atrophy (6,41,42,(45)(46)(47)59), atrophy in soleus muscle of mice composed of fast-twitch fibers mainly was also observed in all types of mice, as was reported elsewhere (40,48,55). The unloading-related decreases in fiber length and sarcomere number may be associated with the remodeling of muscle fibers and sarcomeres, as was reported before (20,59).…”
Section: Responses To Unloadingsupporting
confidence: 54%
“…Exposure to microgravity or hind limb unloading of rodents causes passive shortening of soleus muscle due to ankle plantarflexion (20,39,59), which reduces the mechanical stress (20) and neural activity (19,20,39,43). Even though it is well-reported that muscles composed predominantly of slowtwitch fibers are more susceptible to unloading-related atrophy (6,41,42,(45)(46)(47)59), atrophy in soleus muscle of mice composed of fast-twitch fibers mainly was also observed in all types of mice, as was reported elsewhere (40,48,55). The unloading-related decreases in fiber length and sarcomere number may be associated with the remodeling of muscle fibers and sarcomeres, as was reported before (20,59).…”
Section: Responses To Unloadingsupporting
confidence: 54%
“…Moreover, given that EUK-134 mitigated unloading-related upregulation of oxidative stress, we propose nNOS translocation in response to mechanical unloading in skeletal muscle is a redox-dependent phenomenon. nNOS translocation has previously been associated with increased FoxO3a activation and MuRF-1 activation and muscle atrophy during ground hindlimb unloading (42) and during 91 days of spaceflight (33). In contrast, a new publication indicates that nNOS is necessary in triggering an anabolic signaling pathway involving Nox4 and mTOR, which responds to overloading and regulates muscle hypertrophy (15).…”
Section: Discussionmentioning
confidence: 99%
“…However, at the extremes, a few studies have shown reductions in fiber CSA of between −30% and −55% (Agostini et al, 1991;Steffen et al, 1991). In stark contrast to other models of muscle atrophy (Sandona et al, 2012;Trappe et al, 2004;Widrick et al, 1997), slow oxidative fibers during hibernation do not atrophy more than fast glygolytic fibers. Collectively, these studies indicate that losses of muscle mass, protein and fiber size are typically small during hibernation.…”
Section: Morphological Changes During Hibernationmentioning
confidence: 90%